ETHNIC NETWORKS IN REPRESENTATIONS OF PERMANENT RESIDENT MIGRANTS’ FAMILY MEMBERS LIVING IN ARMENIA - Mnatsakanyan, Lilit; Galstyan, Mihran (Modern Psychology, 2022)
Migrants’ ethnic network – co-ethnics of migrants that are already established in the host country- often play a major role in the migration-decision making process, as well as in the process of migrants’ adaptation in the new host country. Most of the migrants leaving for permanent residence are labour migrants, whose family members continue to live in Armenia. The aim of our research is to study the representationsof ethnic networks and attitude towards them among family members of the permanent resident migrants who live in Armenia.The research is based on qualitative methodology with application of semi-structured interviews and nonparticipative observation methods. The research was carried out with 23 people whose at least one family member emigrated for permanent residency. As a result of theresearch, three main axes characterizing the representations of ethnic networks and attitude towards themamong migrants’ families were distinguished: first, the representation of ethnic networks as a source of help and security, second, high expectations of ethnic networks’ members, and, third, the contradictory attitude towards ethnic networks. We can conclude that ethnic networks can be a certain protective factor in a migrant’s family members’representations, even a substitute for the family, towards which often inadequately high expectations and contradictory attitude are formed.
Keywords: migration; ethnic network; representations; attitude; family.